Universal Newborn Screening for Congenital Cytomegalovirus Infection – From Infant to Maternal Infection: A Prospective Multicenter Study - Chiereghin, Angela; Pavia, Claudia; Turello, Gabriele; Borgatti, Eva Caterina; Baiesi Pillastrini, Federico; Gabrielli, Liliana; Gibertoni, Dino; Marsico, Concetta; De Paschale, Massimo; Manco, Maria Teresa; Ruscitto, Antonia; Pogliani, Laura; et al. (Frontiers in Pediatrics, 2022)
Introduction:Most infants at risk for cytomegalovirus (CMV)-associated sensorineural hearing loss (SNHL) are unrecognized because of the absence of a universal neonatal CMV screening. The search of CMV-DNA by molecular methods in salivary swabs was demonstrated to be a reliable approach. This study describes results obtained by carrying out a universal screening for congenital CMV (cCMV) infection including all live born newborns in 3 Italian sites, as well as the therapeutic interventions and clinical outcome of the CMV-infected neonates. Moreover, CMV maternal infection’s characteristics were evaluated. Methods:To confirm or exclude cCMV infection, a CMV-DNA positive result on a first salivary swab was followed by a repeated saliva and a urine sample collected within 21 days of age. Breastmilk samples were also collected. The search of CMV-DNA was performed with a single automated quantitative commercial real-time PCR assay, regardless of the type of samples used . Results:A total of 3,151 newborns were enrolled; 21 of them (0.66%) were congenitally infected (median saliva viral load at screening, 6.65 [range, 5.03-7.17] log10 IU/mL). Very low/low viral load in screening saliva samples (median value, 1.87 [range, 1.14-2.59] log10 IU/mL) was associated to false positive results (n=54; 1.7%). CMV-DNA was detected in almost half of the breastmilk samples of mother-infant pairs with a false positive result suggesting that contamination from breastmilk may not be the only explanation in the study population. cCMV infection confirmation with the search of CMV-DNA in a urine sample proved to be the gold standard strategy, since false positive results were observed in 4/54 (7.5%) of the repeated saliva samples. Symptomatic cCMV infection was observed in 3/21 (14.3%) infants; notably one (4.7%) developed moderate unilateral SNHL at 5 months after birth. Finally, 2 symptomatic cCMV infections were associated with primary maternal infection acquired in the first trimester of gestation; one newborn with severe cCMV symptoms was born to a mother with no CMV-checkups in pregnancy. Conclusions:Without universal neonatal CMV screening, some infected infants who develop late neurologic sequelae may not be recognized and consequently they are not able to benefit early of instrumental and therapeutic interventions to limit and/or treat CMV disease.